Kulturowy kontekst gatunków publicystycznych a ich wzorzec tekstowy - Rejter, Artur (Stylistyka, 2002)
Tlte article shows that text models o f speech genres are connected with cultural context. There are two journalistic genres described in the article: physiological essay and reulleton. The text model of physiological essay is relatively stabilized, which is connected with its ephemeral character and its scientific inspirations. As for feuilleton, its text model is far more unreStricted,because that speech genre is explicitly inspired by belle[1]There is a difference between physiological essay and feuilleton in the communication process, too. The first speech genre was to objectivize the reality and the second one is to subjectivize it.